2012
DOI: 10.1890/11-0504.1
|View full text |Cite
|
Sign up to set email alerts
|

Niche evolution across spatial scales: climate and habitat specialization in California Lasthenia (Asteraceae)

Abstract: Abstract. Ecologists and evolutionary biologists perceive the ecological niche as a multidimensional relationship between an organism and its environment. Yet, we know little about the degree to which multiple niche axes evolve in concert across various spatial scales to explain differences in distribution patterns and habitat specialization among lineages. Here we used contemporary phylogenetic approaches to analyze the evolution of species' distributions across multiple spatial scales in Lasthenia, a young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 89 publications
(91 reference statements)
2
57
0
Order By: Relevance
“…Vertical zonation of individual pools is often evident from concentric bands of different herbaceous taxa associated with distinct soil conditions that have been shown to represent distinct niche space (e.g., Emery et al 2009). Phylogenetic analysis of different niche components in Lasthenia indicated that the vernal pool depth niche was more evolutionarily conservative than the climate niche; that is, dispersal between pool systems in different climatic regions was more commonly associated with diversification than ecological shifts in pool zonation (Emery et al 2012). Diversification in vernal pools has been associated with increasing specialization to an amphibious life history and associated evolutionary change in photosynthetic pathway in the C 4 grass tribe Orcuttieae, with the most ancestral condition retained in Neostapfia, the sister group to the other two vernal pool genera, Orcuttia and Tuctoria (Boykin et al 2010), and with loss of Kranz anatomy in submerged juvenile foliage of the more highly amphibious Orcuttia (Keeley 1998).…”
Section: Evolution Across Habitat Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical zonation of individual pools is often evident from concentric bands of different herbaceous taxa associated with distinct soil conditions that have been shown to represent distinct niche space (e.g., Emery et al 2009). Phylogenetic analysis of different niche components in Lasthenia indicated that the vernal pool depth niche was more evolutionarily conservative than the climate niche; that is, dispersal between pool systems in different climatic regions was more commonly associated with diversification than ecological shifts in pool zonation (Emery et al 2012). Diversification in vernal pools has been associated with increasing specialization to an amphibious life history and associated evolutionary change in photosynthetic pathway in the C 4 grass tribe Orcuttieae, with the most ancestral condition retained in Neostapfia, the sister group to the other two vernal pool genera, Orcuttia and Tuctoria (Boykin et al 2010), and with loss of Kranz anatomy in submerged juvenile foliage of the more highly amphibious Orcuttia (Keeley 1998).…”
Section: Evolution Across Habitat Islandsmentioning
confidence: 99%
“…Growing appreciation for the importance of ecology in understanding evolutionary change and recent evidence indicating evolutionary decoupling of niche parameters warrants more attention to resolving the history of ecological factors in a phylogenetic context as well (e.g., Emery et al 2012, Töpel et al 2012, Arrigo et al 2013, Anacker & Strauss 2014, in part to characterize likely future responses of lineages to environmental change. Field-based descriptive and experimental work is invaluable to these goals and, although often difficult and unavoidably slow, continues to be the source of some of the most important contributions to evolutionary understanding of the California flora (e.g., Ramsey et al 2003, Angert & Schemske 2005, Lowry et al 2008.…”
Section: Wwwannualreviewsorg • Origins Of Californian Plant Diversimentioning
confidence: 99%
“…[22][23][24][25]. Experiments with an explicit phylogenetic framework can address aspects of trait evolution, niche conservatism, adaptation, historical contingency, exaptations, phylogenetic lag, and genetic constraints (20,(26)(27)(28)(29)(30). Here, we expand on these approaches by also incorporating extensive ecological data collections taken across field sites occupied by members of a whole clade, and integrating them with common garden greenhouse experiments and phylogenetic hypotheses.…”
mentioning
confidence: 99%
“…Fine-scale analyses of the distribution pattern of sympatric species would be of particular interest so that habitat use and fine-scale drivers of species distributions could be examined (see Emery et al 2012). Studies of this nature for Neotropical plant clades would be of particular interest given the high levels of diversity encountered in this region and the limited amount of ecological, evolutionary, and biogeographical studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear, that species ranges are determined by a set of abiotic and biotic conditions that are known as a species niche (Hutchinson 1957) which, together with historical factors, seem to have shaped present-day distribution patterns. In this context, it is critical that analyses of niche elements incorporate information on the phylogenetic history of the focal taxa so that a more complete picture of the factors shaping species distributions can be achieved (e.g., Rice et al 2003;Knouft et al 2006;Eaton et al 2008;Kozak & Wiens 2010;Emery et al 2012;Nyári & Reddy 2013). Niche studies based on robust phylogenetic frameworks allow us to identify how long-term evolutionary processes have led to present-day distribution patterns as well as to establish how species niches have changed and evolved over time (Wiens 2011).…”
Section: Introductionmentioning
confidence: 99%